Electroacupuncture Inhibits Neuronal Autophagy and Apoptosis via the PI3K/AKT Pathway Following Ischemic Stroke - Wang, Man-Man; Zhang, Min; Feng, Ya-Shuo; Xing, Ying; Tan, Zi-Xuan; Li, Wen-Bin; Dong, Fang; Zhang, Feng (Frontiers in Cellular Neuroscience, 2020)
Electroacupuncture (EA) is a safe and effective therapy for ischaemic stroke in both clinical and laboratory settings. However, the underlying mechanism behind EA treatment for stroke still remains unclear. Here, we aimed to evaluate whether EA treatment at the acupoints of Zusanli (ST36) and Quchi (LI11) exerted a neuroprotective effect on ischaemic stroke rats by modulating autophagy and apoptosis via the PI3K/AKT/mTOR signalling pathway. EA was performed at 24 h following brain ischaemia/reperfusion (I/R) for 30 minutes per day for 3 days. Our results indicated that EA treatment significantly decreased neurological deficits and cerebral infarct volume in ischaemic stroke rats. In addition, EA intervention markedly reduced neuronal apoptosis by suppressing the activation of cleaved caspase-3 (CCAS3) at 72 h following I/R, as shown by a Western blot analysis. Furthermore, EA treatment after ischaemic stroke suppressed the ischaemia activated expression level of LC3II/I and Atg7 and increased the ischaemia inhibited expression level of PI3K, phosphorylation of mTOR, phosphorylation of AKT, P62 and LAMP1, hence mediating the autophagy level of the neurocyte, which was reversed by the PI3K inhibitor Dactolisib. In summary, our results indicate that the protective effects of EA treatment at points of Quchi (LI11) and Zusanli (ST36) in rats following cerebral I/R injury was associated with the inhibition of neuronal apoptosis and autophagy via activating the PI3K/AKT/mTOR signalling pathway.